Contraceptive use among adolescent girls and young women ages 15–24 in seven high HIV prevalence countries - Greenleaf, Abigail R.; Sachathep, Karam; Geisler, Emma; Abularrage, Tara F.; Reid, Giles A.; Ndagije, Felix; Nkumbula, Tepa; Nuwagaba-Biribonwoha, Harriet; Abrams, Elaine; Philip, Neena M. (Frontiers in Reproductive Health, 2025)
BackgroundAdolescent Girls and Young Women (AGYW; ages 15–24) continue to use contraceptives at lower rates than older women in sub-Saharan Africa. We describe contraceptive use among AGYW in seven Southern African countries (Botswana, Eswatini, Lesotho, Malawi, Mozambique, Zambia and Zimbabwe).MethodsCross-sectional, nationally representative household-based data from seven Population-based HIV Impact Assessment surveys (conducted between November 2019 and February 2022) were analyzed using survey weights to create descriptive results and pooled odds of modern contraceptive use.ResultsAmong the 11,094 AGYW, contraceptive use (male or female sterilization, IUD, implants, injectables, pills, condoms) ranged from 45.0% in Mozambique to 75.1% in Botswana. Condoms were the most frequently reported method in four of seven countries (Botswana 61% of those using modern methods use condoms, Eswatini 66%, Lesotho 49% and Mozambique 33%). Dual method (use of any modern contraceptive method plus a condom) ranged from <1% in Malawi to 15% in Botswana. When conducting a pooled multivariable logistic regression, higher odds of modern contraceptive use was associated with higher education [Odds Ratio (OR) 1.7, 95% Confidence Interval (CI) 1.5–2.0], being in the highest wealth quintile (OR 1.5, 95% CI 1.2- 2.0), and having children (one birth: OR 2.0 95% CI 1.7–2.4), two or more: (2.5, 95% CI 2.0–3.0), but was lower among AGYW living with HIV (OR 0.7 95% CI 0.6–0.9).ConclusionsContraceptive prevalence rates varied by country but across countries, AGYW in Southern Africa commonly use short-acting methods, and specifically condoms: a user-dependent method prone to inconsistent use. Efforts to expand access to diverse, youth-friendly contraceptive options - particularly short-acting and multipurpose methods - could better align with the needs of AGYW. These findings can inform policies and programs aiming to reduce unmet contraceptive need and improve reproductive health outcomes among AGYW in the region.